Analysis of the Relationship Between Neonatal Intensive Care Nurses' Team Work and Parent Participation Attitudes - Coskun Simsek, Didem; Gunay, Ulviye (Ataturk Univ, 2022)
Objective: This study was conducted to find out the relationship between neonatal intensive care nurses' attitudes about teamwork and their attitudes about parent participation. Methods: This descriptive study was conducted with 120 nurses working in the neonatal intensive care unit between November 2019 and April 2020. The Demographic Information Form, Teamwork Attitudes Questionnaire (TAQ), and Parent Participation Attitude Scale (PPAS) were used to collect the research data. For data analysis, descriptive statistical methods, Mann-Whitney U, Kruskal-Wallis, Spearman's correlation test, and simple linear regression were used. Results: TAQ score averages (107.09 +/- 14.63) and PPAS score averages (84.98 +/- 7.31) of neonatal nurses were found to be high. The difference between nurses' age, marital status, level of education, and average daily number of patients they provided care for and their average TAQ score was found to be significant (P <.05) and the difference between nurses' demographic information and their average PPAS scores was not significant (P >.05). A positive weak association was found between nurses' average TAQ total score, average Team Structure and Communication subdimension scores and their average PPAS scores. A positive moderate association was found between nurses' average PPAS score, average Situation Monitoring sub-dimension score (P <.05). Conclusion: This study found that neonatal nurses support teamwork and parent participation. Teamwork perception and parent participation are important practices that can increase the quality of care in neonatal intensive care units, enable early discharge, and increase the satisfaction of the healthcare team and the family. These approaches should be reinforced in neonatal intensive care units and in all pediatric services in order to increase the quality of patient care.
Yenidoğan Yoğun Bakım Hemşirelerinin Ekip Çalışması ve Ebeveyn Katılımı Tutumları Arasındaki İlişkinin İncelenmesi
Keywords: Teamwork; parent participation; neonatal nurse